Iron-based advanced oxidation processes for enhancing sludge dewaterability: state of the art, challenges, and sludge reuse - Liang, Jialin (2022)
The increasing amount of sewage sludge produced in wastewater treatment plants (WWTPs) poses a great challenge to both environment and economy globally. As a requisite process during sludge treatment, sludge dewatering can significantly minimize the sludge volume and lower the operational cost for downstream transportation and disposal. Iron-based advanced oxidation process (AOP), a robust and cost-effective technique with relatively low technical barriers for high-level sludge dewatering, has been widely explored in the past 20 years. The development was mainly driven by the demands of efficient and sustainable sludge conditioning technology and the flexible sludge management approaches. The application of iron-based AOPs in sludge dewatering process attracts more and more attention. In this work, we discussed the current application of iron-based AOPs technology in the sludge dewatering processes in a holistic manner, summarized the factors affecting the sludge dewaterability in the treatment processes, and analyzed the mechanisms of iron-based AOPs to improve dewatering processes. Furthermore, we elaborated potential advantages, limitations, and challenges associated with implementing iron-based AOPs in the full-scale plants and shared the opportunities for sludge reutilization. This review aims to contribute to the development of highly efficient iron-based AOPs for sludge dewatering and offer perspectives and directions towards the new-generation of WWTPs with the sustainable and eco-friendly benefits.